Analisis Pengendalian Banjir DAS Kasiping Kota Bantaeng Sulawesi Selatan - Anggraeny, Nur Syifa; Yusuf, Andi Rumpang; Cangara, Satriawati (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Flooding is a situation where an area is inundated by water, which causes significant losses both morally and materially. This research was carried out in Bantaeng City, Bonto Tiro village, precisely in the Kasiping watershed, with the aim of analyzing the amount of rainfall and flood discharge for return periods of 25, 50 and 100 years as well as analyzing flood control methods. In planning regional average rainfall using the algebraic average method then calculating the planned rainfall using the log pearson type III method and the gumbel method. To strengthen the distribution selection, the Chi-square test and the Smirnov Kolmogorof test were used, then an analysis of the planned flood discharge was carried out using the HSS Nakayasu method. Based on calculations, the flood discharge for the 25 year return period (Q25) is 46.75 m3/sec, the 50 year return period (Q50) is 56.51 m3/sec, the 100 year return period (Q100) is 67.74 m3/sec. To overcome flood problems, one of the flood control methods used is the construction of a check dam upstream with a storage volume of 269,340 m3.